(untitled) (Journal of Geography and Environmental Management, 2025)
In this paper the theoretical and methodological aspects of migration processes research, focusing specifically on "labour migration" are examined, theories of migration of population and workforce by domestic and foreign scholars are analyzed. Historical periods of the development of labour migration in Kazakhstan and the main trends of external labour migration in the modern era are discussed. The characteristics, motives, distinctive features, types, and indicators of labour migration are highlighted. Special attention is given to identifying the primary reasons and factors of external labour migration. The directions of migration in Kazakhstan and the main sectors attracting foreign labour are analyzed. External labour migration in Kazakhstan is presented as a result of socio-economic development and implemented migration policies. As a result of the study, it is concluded that Kazakhstan is a recipient country within the post-Soviet space; with its labour market being supplemented by foreign labour and low-skilled labour immigrants primarily from Central Asian countries. A notable feature of the flow of labour migration from Central Asian republics to Kazakhstan is a high proportion of illegally employed among them. At the same time, one of the significant trends in external labour migration is the decrease in the emigration of compatriots alongside a substantial outflow of skilled professionals, in other words "brain drain." It is noted that despite the existence of numerous scientific studies on migration, the aspects of labour migration i0n the Republic of Kazakhstan remains insufficiently presented